An Updated Review of Thermal Ablation Technology for Uterine Fibroids and Adenomyosis: Focusing on Protecting Fertility - Zhang Q; Liang X; Chen Z (Dove Medical Press, 2024)
Qing Zhang,1,2,* Xiaowen Liang,1,2,* Zhiyi Chen1- 3 1Key Laboratory of Medical Imaging Precision Theranostics and Radiation Protection, College of Hunan Province, the Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, People's Republic of China; 2Institute of Medical Imaging, Hengyang Medical School, University of South China, Hengyang, People's Republic of China; 3Department of Medical Imaging, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhiyi Chen, Key Laboratory of Medical Imaging Precision Theranostics and Radiation Protection, the Affiliated Changsha Central Hospital, 161 Shaoshan Road, Changsha, 410004, Hunan, People's Republic of China, Email zhiyi_chen@usc.edu.cnAbstract: There is a growing trend towards minimally invasive or noninvasive alternatives for gynecological disorders due to their rapid alleviation of symptom, expedited recovery, and minimal risks of postoperative complications. Thermal ablation technology has been commonly advocated as a minimally invasive therapeutic methods in recent years, including microwave ablation, radiofrequency ablation, and high-intensity focused ultrasound. The increasing application scenarios require updated and systematic research, and more evidence to promote their appropriate use. The objective of this review is to summarize the latest views of ablation from a prospective of fertility protection, endeavor to clarify the clinical value of thermal ablation technology in protecting fertility by assessing parameters such as ablation rates, alleviation of disease symptoms, re-intervention rates and post-treatment pregnancy rates. We review the clinical studies of ablation for uterine fibroids and adenomyosis treatment in the past 10 years, summarize the limitation and the prospects of its development in the treatment process, so as to provide clinicians with advice on the best practice. In the management of uterine fibroids and adenomyosis, thermal ablation technology offers improved fertility preservation and minimizes normal tissue injury compared to traditional surgical approaches for patients pursuing reproductive goals. In the future, thermal ablation technology will play a significantly enhanced role in preserving fertility for individuals requiring treatment for uterine fibroids and adenomyosis, guided by indications. But further research is still needed in the form of more extensive randomized prospective trials to provide stronger evidence supporting this perspective.Keywords: fertility protection, radiofrequency ablation, microwave ablation, high-intensity focused ultrasound, uterine fibroids, adenomyosis